1] ⬇
p - (6 - 2(q))➡0
p + 2q - 6➡0
q = 3 because 6÷2 = 0
p = 6 because 6 ÷ 1 = 6
Slope ➡ 0.5
-----------------------------------------------------------------
2] ⬇
p - (1 + q)➡0
p - q- 1➡0
Q = -1 because 1 ÷ -1 ='-1
P = 1 because 1 ÷ 1 = 1
Slope ➡ 1
Answer:
D
Step-by-step explanation:
step 1: find the slope
slope is 2/-4 = -1/2
then plug in the value for x to y, you get +1 for the y intercept
then it becomes y=-1/2x + 1
I hope this answer helped, and if it was correct, please mark this as brainliest! Thank you!
The answer to ur question is a
1/5 divided by 5/7 is 7/25
1/5 ÷ 7/5 = 7/25
Your answer is 7/25